Location-specific heterogeneity in landslide resilience index: A household-based comparative study in Rangamati Hill District, Bangladesh - Raihan Riaz; Neegar Sultana; Raihan Riaz (Ecological Indicators)
The study initially proposes an indicator-based approach for assessing location-specific variations in landslide resilience to minimize landslide risk by building a resilient society in Rangamati Hill District (RHD). Secondly, the research constructed a household-level Landslide Resilience Index (LRIH) based on four dimensions of resilience: social, economic capital, physical, and environmental systems. After reviewing the literature, two Focus Group Discussions, and 10 Key Informant Interviews, 48 location-specific variables were utilized to create the LRIH, which entails 19 indicators. Finally, 294 household heads from eleven landslide-prone hills were interviewed using a semi-structured questionnaire. Dimension-based indexes for each household were created by subjectively weighting categorical data and standardizing continuous variables. To construct and map the LRIH, composite scores of four dimension-based index were normalized using min–max techniques, and rescaled into 0 and 1. The result identified that only 4.8 % of households in the study area obtained a high level of LRIH. The findings also exhibited that out of the eleven study sites, Gorjontoli (μ = 0.63) and Rupnagar (μ = 0.26) ranked first and eleventh, respectively, in terms of LRIH. The spatial pattern revealed that households located in proximity to urban areas received greater resilience in contrast to households situated in the suburbs. The results provide a comprehensive framework for policymakers and academics to build a resilient society against landslides, which may be adopted in comparable regional settings. The findings also contribute to achieving the fourth priority action of the Sendai Framework for Disaster Risk Reduction (2015–2030), which seeks to enhance society’s resilience.